﻿Vitamin D as a drug: new therapeutic approaches - Mohd Alaraj; Fahaad S. Alenazi; Dania Hassan; Ashfaque Hossain (Pensoft Publishers, 2022)
Vitamin D is one of the essential vitamins and has recently been demonstrated to be much more important for the appropriate functioning of the human body and well-being than initially believed. Although vitamin D is mainly known for its link with bone fractures and bone diseases, recent studies revealed that vitamin D and its analogues have revealed many pharmacological actions covering the regulation of cell growth, inhibition of inflammation, and improvement of neuromuscular function and immune function. Moreover, vitamin D and its analogues are reported to have role in different types of cancers, skin diseases, diabetes mellitus and infections caused by different bacterial and viral pathogens including SARS-CoV-2. The goal of this study is to evaluate the scientific literature on therapeutic uses of vitamin D and its analogues against different diseases and health condition. Special attention has been given to COVID-19 infection, cancer, skin diseases, and diabetes. The molecular mechanisms involved are also explored.